2011
DOI: 10.1002/jcla.20484
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic role of serum glypican 3 in patients with hepatocellular carcinoma

Abstract: α-Feto protein (AFP) is the widely used tumor marker in the diagnosis of hepatocellular carcinoma (HCC). The aim of this study was to assess the diagnostic and prognostic validity of a novel marker, serum Glypican-3 (GPC3) and to compare AFP in patients with HCC. One hundred and twenty-eight patients (75 patients with HCC, 55 patients with cirrhosis, and 28 healthy controls) were included in this study. Cut-off value of GPC3 was 3.9 pg/ml. AFP was divided into four subgroups, according to cut-off values with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 17 publications
2
35
1
Order By: Relevance
“…Ozkan H,et al had recently reported that the sensitivity, specificity, and positive and negative predictive values of serum GPC3 was 61.33%, 41.82%, 58.97%, and 44.43%, respectively. It is suggested that serum GPC3 is not a useful diagnostic and prognostic marker for HCC 32 . However, in this study, it is firstly reported that the GPC3L expression was detected in 77.4% of patients with serum AFP negative and in 81.2% of patients with AFP greater or equal to 400µg/L.…”
Section: Resultsmentioning
confidence: 99%
“…Ozkan H,et al had recently reported that the sensitivity, specificity, and positive and negative predictive values of serum GPC3 was 61.33%, 41.82%, 58.97%, and 44.43%, respectively. It is suggested that serum GPC3 is not a useful diagnostic and prognostic marker for HCC 32 . However, in this study, it is firstly reported that the GPC3L expression was detected in 77.4% of patients with serum AFP negative and in 81.2% of patients with AFP greater or equal to 400µg/L.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, glypicans play an important role in growth factor-mediated signal transduction and it is not surprising that they are expressed in tumoral microenvironments (14). In addition, since glypicans mediate the formation of cell-cell and cell-extracellular matrix adhesions, they exert pro-as well as anti-tumorigenic effects (15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Tangkijvanich et al reported that GPC3 and AFP combination yielded 78 % sensitivity [37]. Ozkan et al reported that the sensitivity of GPC3 and AFP combination does not exceed 67 % [13]. Fig.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast to the hepatocytes of healthy individuals and hepatitis patients, many studies reported an increased GPC3 expression in HCC tissues [9]. However, many studies suggested that serum GPC3 is a specific HCC biomarker owing to its higher levels in HCC than that in healthy or hepatitis individuals [10,11]; conflicting results were obtained by other studies [12][13][14]. There is an agreement between most of these studies and others that GPC3 alone is not a promising HCC serum maker.…”
Section: Introductionmentioning
confidence: 91%